Seasonal Trends and Sociodemographic Influences on Long-Distance Trips - A Full Year of GPS Tracking Data from Munich - Nachtigall, Nico; Magdolen, Miriam; Lienkamp, Markus (European Journal of Transport and Infrastructure Research, 2025)
This study provides insights into the rarely observed long-distance travel patterns of individuals. Collected smartphone tracking data from June 2022 to May 2023, focused on the Munich metropolitan region, allows us to investigate travel behavior and the occurrence of long-distance travel throughout the year. After comprehensive data preparation, the recorded modal share and the share of observed long-distance trips are compared with the findings of a German travel survey to investigate the benefits of the dataset. Long-distance trips are further analyzed in terms of their occurrence rate and modal share throughout the year. Furthermore, the influence of various sociodemographic characteristics and car ownership on long-distance travel is explored. The primary usage of privately owned cars is also analyzed. Our findings reveal differences in the occurrence of trips, with increased frequency observed during summer, weekends, school holidays, and public holidays. Additionally, the research underscores the impact of sociodemographic factors, particularly household income and age, on elevated levels of long-distance travel activity. Our research indicates that a significant share of car owners in the urban area use the car primarily for long-distance trips.